Phytochemical Characterization and Antifungal Efficacy of Camphor (Cinnamomum camphora L.) Extract against Phytopathogenic Fungi - Sherien Sobhy; Abdulaziz A. Al-Askar; Elsayed K. Bakhiet; Mohsen M. Elsharkawy; Amr A. Arishi; Said I. Behiry; Ahmed Abdelkhalek (Separations, 2023)
Cinnamomum camphora methanolic extract was tested for antifungal activity against three common, isolated, widespread phytopathogens: Alternaria alternata, Fusarium solani, and Fusarium oxysporum, which were molecularly identified and assigned accession numbers ON795987, ON795988, and ON795989, respectively. At 4000 µg/mL, the highest concentration of C. camphora methanolic extract inhibits the fungal mycelia weight of F. oxysporum, A. alternata, and F. solani by 60, 49, and 24%, respectively. The presence of several bioactive metabolites in the C. camphora extract could explain its antifungal activity. The presence of numerous phenolic and flavonoid compounds in the extract was revealed by HPLC analysis, including catechin and gallic acid, which had the highest concentrations of 6.21 and 6.98 µg/mL, respectively. Furthermore, osmoprotectants, total amino acids, and glycine betaine were abundant. Furthermore, total antioxidant activities, as measured by PMA and DPPH, were significant. The most abundant compound in the extract, according to GC-MS analysis, was mono(2-ethylhexyl) ester of 1,2-benzene dicarboxylic acid. Based on its in vitro efficacy in inhibiting mycelial growth weight, the tested extract could be recommended as a safe fungicide instead of a chemical treatment.